The making of Eurosceptic Britain - Gifford, Chris (Ashgate Pub., 2014)
Chris Gifford offers a radical interpretaton of a major political issue. The book goes beyond existing narrative and institutional accounts of Britain and Europe by presenting a theoretically coherent and unique perspective on a troubled relationship.